INCORPORATION OF RISK ASSESSMENT TOOL IMPACTS PATIENT AND GASTROENTEROLOGIST CONFIDENCE AND TREATMENT DECISION MAKING IN BIONAIVE CROHN'S DISEASE. (26th January 2023) - Ungaro, Ryan; Patel, Anish; Rui, Shumin; Jimenez, Darwin; Helmus, Drew; Gorbenko, Ksenia; Dubinsky, Marla; Keefer, Laurie
Abstract: BACKGROUND: Clinical guidelines recommend the incorporation of risk stratification assessments when making decisions about Crohn's disease (CD) treatment. We aimed to evaluate if patient and gastroenterologist (GI) decision making and confidence about starting or changing therapy were impacted by reviewing a CD risk stratification assessment. METHODS: We conducted a multicenter, prospective study evaluating the impact of a risk stratification tool on decision making by GIs and biologic naïve adult CD patients considering starting or changing therapy. Medical records were reviewed by a GI at the organizing site to determine risk according to the American Gastroenterological Association (AGA) Crohn's Disease Care Pathway risk assessment tool. Patients with any risk factors for rapid disease progression (age<30 at diagnosis, deep ulcers, extensive anatomic involvement, perianal disease, prior CD surgery, and/or stricturing/penetrating behavior) were considered moderate-high risk. Patients and treating GIs were then provided a report with their risk assessment conveyed in both written and visual ("risk gauge") format. Participants were surveyed at baseline and at 7 days after viewing the risk stratification assessment and were unaware which risk assessment tool was used to determine risk. The primary outcome was behavioral change defined as any modification in treatment plan or increase in patient or GI self-assessed confidence in need for treatment change (on 5-point Likert scale) from baseline to day 7. RESULTS: 47 patient-GI pairs were enrolled across 14 sites. Among CD patients, mean age was 40.2 years, 59% were men, 70% were white, 80% had inflammatory (B1) disease behavior, 74% had no prior CD-related hospitalizations, and 82% no prior CD-related surgeries. 64% of patients were deemed moderate-high risk and 36% low risk by AGA criteria. In comparison, 40% of patients self-assessed their risk as moderate-high at baseline. The most common moderate-high risk factors were age<30 (45%) and stricturing/penetrating behavior (20%). At baseline, 49% of GI risk assessments of their patients were discordant with AGA risk stratification (e.g. moderate-high risk by AGA evaluated as low risk). Behavioral change was observed in 52% of participants at day 7 and was similar whether patient was low or moderate-high risk. At day 7, patient confidence increased in 21%, GI confidence increased in 23%, and treatment recommendation was changed in 36% of cases. Among patients assessed as low risk disease, confidence that patient would benefit from treatment change decreased in 47% of GIs and 59% of CD patients at day 7. CONCLUSION: Incorporation of a simple risk stratification assessment when considering treatment change in CD can assist in patient and GI decision making. Low risk assessments are associated with lower confidence in decision making.